Left atrial thrombus in atrial fibrillation/flutter patients in relation to anticoagulation strategy: LATTEE registry. (19th May 2022) - Gawalko, M; Kaplon-Cieslicka, A; Budnik, M; Scislo, P; Piatkowski, R; Kochanowski, J; Opolski, G; Grabowski, M
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Atrial fibrillation (AF) and flutter (AFl) increase the risk of thromboembolism by promoting clot formation in the left atrium. Current guidelines recommend initiation of oral anticoagulation (OAC) with vitamin K antagonists (VKAs) or, preferably, non-VKA-OACs (NOACs) in men and women with a CHA2DS2VASc score of ≥2 and ≥3, respectively. Effective OAC is also recommended 3 weeks before elective AF cardioversion or catheter ablation with pre-procedural ttransesophageal echocardiography (TEE) as an alternative. However, TEE before AF/AFl cardioversion or ablation is often performed even in anticoagulated patients, given that, in clinical practice, "effective" OAC may be difficult to achieve and/or verify. Purpose: The aim of the study was to assess the prevalence of left atrial thrombus (LAT) in AF/AFl in relation to OAC strategy. Methods: The Left Atrial Thrombus on Transesophageal Echocardiography (LATTEE) registry was a prospective, observational study enrolling consecutive patients with AF or AFl in whom TEE was performed before direct current cardioversion or catheter ablation, hospitalized in 13 cardiology departments in Poland. Patients' recruitment process started from November 2018 in the coordinating centre and lasted 12 months since the beginning of the study in each participating centre or longer, i.e., until the inclusion of at least 200 patients at each participating centre (with the last patient enrolled in May 2020). Results: Of 3109 patients enrolled, 88% were on chronic, 1.5% on transient OAC and 10% without OAC. Of patients on chronic OAC, 39% received rivaroxaban, 30% dabigatran, 14% apixaban and 18% vitamin K antagonists (VKA). Patients on apixaban were oldest, had worst renal function and highest both bleeding and thromboembolic risk, and more often received reduced doses. Overall, prevalence of LAT was 8.0% (7.3% on chronic OAC vs. 15% without OAC; p<0.01). In patients on VKA, prevalence of LAT was doubled compared to patients on non-VKA-OACs (NOACs) (13% vs. 6.0%; p<0.01), even after propensity score matching (13% vs. 7.5%; p<0.01) and in multivariable logistic regression (OR 1.9, 95% confidence interval 1.4-2.8). Prevalence of LAT in patients on apixaban was higher (9.8%) than in those on rivaroxaban (5.7%) and dabigatran (4.7%; p<0.01 for both comparisons). However, in propensity score matching and multivariable logistic regression, there was no difference in the risk of LAT between apixaban and other NOACs. Conclusions: Prevalence of LAT in AF is non-negligible even on chronic OAC. In the real-world AF/AFl population, the risk of LAT seems higher on VKA compared to NOAC, and similar between different NOACs.